"What matter who's speaking?" The question of the author in novel L'Événement by Annie Ernaux and film L'Événement by Audrey Diwan - Jovanović Sanja (Reči (Beograd))
Summary: The paper investigates to what extent the idea of death of the author has been transformed and seeks to compare relationships of female authorship. The paper discusses the development of post-structuralist theories of Rolandes Barthes and Michel Faucault that cancel the origin of the narrator, declare the death of the author stating that the meaning is determined by the reader, and question if the identity of the narrator makes a difference at all. The paper further provides an insight into the implications of such cancellation during the seventies and eighties of the last century, and even today, when a large number of objections were raised by theorists of feminist literature, who primarily criticized indifferent attitude of the originators of these ideas towards those who got the right to express themselves relatively late. The paper traces the theory of l'écriture féminine and the ambivalence towards the importance of highlighting gender differences, and also points to the importance of feminist thought in the way in which the reading of texts is approached today. The analysis of the texts demonstrates the uniqueness of female authorship, primarily in the thematic and expressive sense, but also shows the current (and still) necessity of defining female authorship as such in terms of promotion and visibility. However, in terms of collective experience, the analysis proves that it does not matter who speaks, and that one (female) experience can be shared regardless of its origin.